Heterosexism in school: The counselling experience of Chinese tongzhi students in Hong Kong - Kwok, D.; Winter, Sam; Yuen, M. (2012)
The study is part of a larger project involving a phenomenological inquiry into the lived experiences of tongzhi students in Hong Kong public schools. The research question of this article focuses on the counselling experiences of nine Chinese lesbian, gay, bisexual and questioning/queer (LGBQ) students aged 14-18 in Hong Kong Chinese secondary schools. We conducted qualitative data analyses via a software package for data coding and data reduction. Four themes emerged: Feeling fearful: judging my sexuality; Feeling disengaged: omitting my sexuality; Feeling alienated: pathologising my sexuality; Feeling supported: making an effort to understand my sexuality. The findings from the present study inform the development of school counselling within Chinese societies by generating recommendations about counsellors' professional codes of ethics, counsellor training and practice.